Electron emission in grazing-ion-surface collisions - Gravielle, Maria Silvia (2000)
For ions impinging grazingly on a solid surface, the electron emission from the inner shells of solid atoms is investigated by employing a semiclassical formalism. The emission rate is expressed in terms of probabilities of atomic ionization, which are evaluated with the continuum-distorted-wave–eikonal-initial-state approximation, taking into account the full dependency on the impact parameter. The model is applied to the calculation of the differential yield of ejected electrons for fast protons colliding with an aluminum surface. Inner-shell emission is compared with the electron emission from the valence band of the metal, considering different ejection angles. Calculated energy spectra of emitted electrons are in good agreement with the available experimental data.